2013
DOI: 10.1103/physrevlett.111.073904
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Metatronic Nanocircuits by Design

Abstract: Lumped circuit elements (i.e., resistors, capacitors, and inductors) provide the basic building blocks of microelectronic devices ubiquitous in information processing, storage, and communications. The use of these modular quasistatic components can be extended to the nanoscale optical regime to achieve high-density, high-speed analogues of these traditional circuits. We reimagine these devices in the near-infrared (NIR) regime, making use of a simple nanorod geometry and plasmonic transparent conducting oxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 20 publications
1
63
0
Order By: Relevance
“…May we still obtain the desired parameter values by properly combining and sculpting the two given constituent materials with different parameters, particularly when the desired parameter values are vastly different from those of the constituent materials? Indeed, this quest is consistent with the notion of metamaterials, and many examples of metamaterials constructed in the past decade by various research groups worldwide have been built using a limited number of materials [17][18][19][20][21][22][23][24] . However, here we develop the notion of digital metamaterials in order to demonstrate that with only two properly chosen elemental materials, coined as "metamaterial bits", at a given range of operating wavelengths, one would, under proper conditions, be able to synthesize composite media with a large range of parameter values.…”
Section: Main Textmentioning
confidence: 81%
“…May we still obtain the desired parameter values by properly combining and sculpting the two given constituent materials with different parameters, particularly when the desired parameter values are vastly different from those of the constituent materials? Indeed, this quest is consistent with the notion of metamaterials, and many examples of metamaterials constructed in the past decade by various research groups worldwide have been built using a limited number of materials [17][18][19][20][21][22][23][24] . However, here we develop the notion of digital metamaterials in order to demonstrate that with only two properly chosen elemental materials, coined as "metamaterial bits", at a given range of operating wavelengths, one would, under proper conditions, be able to synthesize composite media with a large range of parameter values.…”
Section: Main Textmentioning
confidence: 81%
“…The as-fabricated device may be assumed to be composed of a number of building blocks as given in Figure 13. The central region is a quantum dot sandwiched between two potential barriers (dielectrics, being MPA for our device), L being the length of the entire device such that a << L. Fu et al [3] considering a device similar to that of Figure 13 obtained theoretically that for j ξ j < 1 the admittance is always inductive and for j ξ j > 1, admittance of the device is capacitive at low frequencies before crossing over to and inductive behaviour at higher frequency, ξ being a parameter related to the energy and width of the resonance. Fu et al [6] found the quantum inductance to be related to the life time of the quasi-bound state resonance level.…”
Section: Resultsmentioning
confidence: 99%
“…The concepts of distributed electronic circuit components have been applied to optical structures such as transmission lines [153,200], and an analysis of the optical power associated with electromagnetic waves can be related to lumped circuit components [155,156,201]. The lumped circuit description has been demonstrated in the optical regime (below 700 nm) in terms of an inductor-capacitor circuit [155] in the thermal infrared regime (8-14 μm) [202] and mid infrared (above 1.3 μm) [203].…”
Section: Plasmonic Circuitsmentioning
confidence: 99%